2017
DOI: 10.1097/sle.0000000000000467
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Pain After Laparoscopic Repair of Primary Umbilical Hernia: Titanium Tacks Versus Absorbable Tacks: A Prospective Comparative Cohort Analysis of 80 Patients With a Long-term Follow-up

Abstract: We investigated if a novel fixation device with absorbable tacks (Securestrap) causes less early and chronic postoperative pain after laparoscopic repair with a double-crown mesh fixation of ventral abdominal wall hernia when compared with the standard fixation device with nonabsorbable titanium tacks (Protack). The primary outcome measure was early postoperative pain at 2, 6, and 12 weeks postoperatively. The secondary outcome measure was chronic postoperative pain measured ≥18 months after surgery. Pain leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…We used the sutures method for fixing tissues with mesh, but the results of using special fixing devices during the operation were presented also. For example, [ 2 ] indicates postoperative pain syndrome and the need to use painkillers up to 12 weeks after surgery, since the fixing nails are made of polydioxanone, hydrolysis of which is completed within 12–18 months after implantation. Special materials used for fixing meshes, for example, ProGrip TM according to the authors [ 11 ] showed a satisfactory (average) fixing strength of 1.3 N/cm (±STE 0.2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used the sutures method for fixing tissues with mesh, but the results of using special fixing devices during the operation were presented also. For example, [ 2 ] indicates postoperative pain syndrome and the need to use painkillers up to 12 weeks after surgery, since the fixing nails are made of polydioxanone, hydrolysis of which is completed within 12–18 months after implantation. Special materials used for fixing meshes, for example, ProGrip TM according to the authors [ 11 ] showed a satisfactory (average) fixing strength of 1.3 N/cm (±STE 0.2).…”
Section: Discussionmentioning
confidence: 99%
“…The increasing number of abdominal surgeries leads to an increasing number of IVH. According to different authors, incisional ventral hernias and recurrent abdominal hernias are likely to occur in 2–20% cases after laparotomies and postoperative complications [ 1 2 ]. Most often, IVH develops after gynecological surgeries (26–50% incidence) and biliary tract interventions (20–30% incidence) [ 1 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary outcome measures of most studies (recurrence, patient satisfaction and pain) suffer from lack of standardization in definition 9 10 and measurement. 11 Follow-up tends to be short relative to the usual time-scale of recurrence development. 12 …”
Section: Methodology and Limitations Of Studiesmentioning
confidence: 99%
“…6 The EHS/AHS guidelines state that this decision should be taken on a case-by-case basis. 1 Although not unanimous, the main studies in this field support the safety of synthetic mesh in this environment (►Table 11).…”
Section: Required Removal Of Large Meshmentioning
confidence: 98%